Fourth Year Hon. Mention: The Manipulation of Long and Short Temporalities in Bamewawagezhikaquay’s “The Contrast”: EN 4061, Studies in Ecocriticism: Environmental Justice Literature. Course Director: Katarina O’Briain - Nisi, Amanda (Noteworthy: The LA&PS Writing Prizes, 2025)
“The Manipulation of Long and Short Temporalities in Bamewawagezhikaquay’s ‘The Contrast’” highlights the effectiveness and power of close textual analysis to critically and creatively find meaning at the level of the text that opens up greater layers of meaning, from language to theme to ideology. The author situates the analysis in the application of an ecocritical theory of time and its application to a poem by Bamewawagezhikaquay (Jane Johnston Schoolcraft). The theoretical framework presents a guide for the close analysis of the poem in a thoughtful and precise way: through word choice, theme, imagery, and symbolism, the author underscores competing concepts of time in the poem and how these come to underscore an ideological critique against the European colonial forces that disrupted Indigenous peoples in North America. The author effectively grounds the essay and its analysis with an explicitly political lens, and this is enforced in the ensuing ideological analysis of the poem (in that use of time). Ultimately, it is in navigating the different perspectives in the poem - settler and speaker, Indigenous and colonial, personal and collective, “short time” and “long time” - that show how even the smallest of word choices shows a wealth of meanings and ideological implications, revealing the depth of the poem’s critique.